Ethical Implications of Autonomous Decision-Making Systems (Journal of Ethics in Emerging Technologies & Society p-ISSN 3117-5996 and e-ISSN 3117-6003, 2025)
Autonomous decision-making systems -- AI agents that take consequential actions without human approval at each step -- are increasingly deployed in domains from financial trading to medical triage to military target identification, raising profound ethical questions about accountability, moral responsibility, meaningful human control, and the appropriate scope of machine agency over decisions affecting human welfare. This paper proposes the Autonomous Decision-Making Ethics Framework (ADMEF), a systematic analysis of five ethical dimensions -- moral responsibility attribution, meaningful human control, value alignment under distribution shift, dignity and consent in autonomous interaction, and systemic autonomy risk -- applied to six autonomous decision-making domains: autonomous vehicles, algorithmic trading, medical AI diagnosis, criminal justice risk assessment, military autonomous weapons, and AI-driven social services allocation. ADMEF introduces the Autonomy Ethics Risk Score (AERS) integrating harm severity, accountability gap, consent deficit, and value alignment difficulty, and evaluates each domain through structured expert analysis (16 AI ethicists, legal scholars, and domain specialists) and case study analysis. Key results: military autonomous weapons achieve the highest AERS (0.964) -- the most ethically intractable autonomous domain; criminal justice AERS = 0.908 driven by accountability gap and consent deficit; medical AI AERS = 0.796 (high but manageable through informed consent and human oversight); meaningful human control is the most critical ethical safeguard across all domains. The framework provides autonomous system ethical governance guidance across domains.